Design and fabrication of a vacuum forming machine: to design and fabricate a vacuum forming machine for forming dental aligners - Chia, Andrew Weizhi (2016)
Current treatment costs for teeth alignment procedures are high despite of recent developments in the field of orthodontics. This report describes a project to design and fabricate an improved vacuum forming machine to form dental aligners. The main objective is to provide an alternative low-cost method for teeth alignment that can also be done domestically by an individual. This report will cover an overview of the properties of different types of principles and techniques behind the moulding of a thermoplastic sheet. Research on existing designs and prototypes are to be studied, leading to a new conceptual design. The proposed vacuum forming machine consists of a clamp to hold the thermoplastic sheet while it is being heated by a heating gun and subsequently lowered over a mould to form the dental aligner using suction provided by a household vacuum cleaner. The vacuum former is portable, thus being suitable for domestic use. Various parameters controlling the suction and heating of the vacuum former are to be explored, and subsequently optimized for the optimal results. Experiments on the proposed conceptual design are to be conducted to evaluate the most effective range of parameters to form the aligner. Mathematical models are also used to compute the optimal results for the different parameters used in the experiments. The design is able to determine the optimal results for moulding a thermoplastic sheet. However, the final design of the vacuum forming machine will need to be refined with further testing and evaluations.